Exploring the Scientific Output and Impact of Universitas Muhammadiyah Surakarta: A Bibliometric Analysis - Saky, Sheikh Abu Toha Md; Isam, Md. Nurul (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2024)
This study uses bibliometric techniques to evaluate the scientific output of Universitas Muhammadiyah Surakarta (UMS), addressing a common challenge for regional universities: limited global visibility. Despite demonstrating strong research productivity, with 1,389 publications from 2004 to 2022, UMS’s influence remains primarily regional, as evidenced by a high concentration of local citations. By analyzing citation metrics, co-authorship networks, and publication trends, this study sheds light on UMS’s strengths and areas for development. The findings show that UMS excels in fields like public health and engineering, supported by partnerships with institutions in Malaysia and the UK. However, fields such as social sciences and education have lower international citation rates. This research highlights the need for UMS to pursue interdisciplinary collaborations, broaden its network beyond Southeast Asia, and aim for publication in high-impact journals to enhance its global presence. By providing strategic recommendations, this study contributes to knowledge on regional university research performance, suggesting future analyses that incorporate additional databases and multilingual data for a more comprehensive view of UMSâ€™s contributions to the global academic community.